Inflammation down-regulates CYP3A4-catalysed drug metabolism in hemodialysis patients - Hadi Molanaei; Abdul Rashid Qureshi; Olof Heimbürger; Bengt Lindholm; Ulf Diczfalusy; Björn Anderstam; Leif Bertilsson; Peter Stenvinkel (BMC, 2018)
Abstract Background Recent studies indicate that inflammation may also affect CYP3A4 activity. Associations of CYP3A4-mediated metabolism of quinine, with inflammatory biomarkers were investigated in patients undergoing maintenance hemodialysis (HD). Methods A single dose of 100 mg quinine was given to 44 HD patients and the plasma concentration of quinine and its metabolite 3-OH-quinine were measured 12 h after drug intake. The ratios of quinine/3-OH-quinine and 4β-OH-cholesterol/cholesterol were used as markers of CYP3A4 activity. Inflammatory biomarkers, high-sensitive CRP (hsCRP), pentraxin 3 (PTX3) and orosomucoid were followed during 4 weeks prior to quinine administration. Results The quinine/3-OH-quinine ratio correlated with median concentrations of hsCRP (Rho = 0.48; p = 0.001) and orosomucoid (Rho = 0.44; p = 0.003), and also with interleukin-6 at 12 h after drug intake (Rho = 0.43; P = 0.004) but not PTX3. In multivariate regression analysis, the correlation between CYP3A4 activity and median hsCRP remained borderline significant (p = 0.05). 4β-OH-cholesterol/cholesterol ratio correlated with quinine/3-OH-quinine (p = 0.008), but not with any of the inflammation markers. Conclusions The association between CYP3A4 activity and inflammatory biomarkers suggest that the activity of CYP3A4 is reduced by inflammation in HD patients. Further studies are needed to confirm this finding and to assess to what extent magnitude and duration of inflammation as well as the microbiota affect drug metabolism.